The Incidence of Thyroid Carcinoma in Multinodular Goiter: A Retrospective Study - Shrestha, D.; Shrestha, S. (Journal of College of Medical Sciences-Nepal, 2015)
Background and Objective: To determine the incidence and the types of various thyroid malignancies in multi-nodular goiter. Material and methods: This is a retrospective study, conducted in Department of ENT and Head and Neck Surgery, National Academy of Medical Sciences Bir Hospital Kathmandu and Alka Hospital Pvt. Ltd Lalitpur. The study period was 3 years from 11 January 2011 to 10 January 2014. The study population consisted of 100 patients who were diagnosed as a multinodular thyroid nodule. Result: The highest frequency was 50 (50%) in 31-40 years. Among the total cases, 28 (28%) were males and 72(72%) females. Histopathological analysis showed that benign multi-nodular goiter was present in 87 (87%) cases, and malignant thyroid lesion in 13 (13%) cases. Among malignancies, papillary carcinoma was found as the commonest malignancy 11 (84.61%) cases followed by follicular carcinoma 1 (7.69%) case and anaplastic carcinoma 1(7.69%) case. Conclusion: The risk of malignancy in multinodular goiter should not be underestimated as significant number of patients with thyroid malignancies present with multinodular goiter. JCMS Nepal 2014; 10(4):18-21